The Biological Disappearance Rate of Prothrombin, Factors VII, IX and X from Plasma in Hypothyroidism, Hyperthyroidism, and During Fever - Loeliger, E. A; van der Esch, B; Mattern, Mieke J; Hemker, H. C (Thrombosis and Haemostasis, 1963)
The biological disappearance rate of coagulation factors II, VIT, IX and X from plasma is decreased in myxoedema and increased in thyreotoxicosis. In patients with elevated body temperatures, an increase of up to three times the normal rate was observed. The clinical implications of these findings are briefly discussed.